The relationship between directors' remuneration and company performance : a study on public listed companies in Bursa Malaysia - Lee, Jeng Nam, 1989-, author; Norkhairul Hafiz Bajuri, supervisor; Fakulti Pengurusan dan Pembangunan Sumber Manusia (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2013)
Project Paper (Sarjana Muda (Perakaunan)) - Universiti Teknologi Malaysia, 2013